Condylar height in complete dentition patient seen through panoramic radiograph: observational study - Putri, Sekar Kinanti Dania; Sam, Belly; Damayanti, Merry Annisa (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACT Introduction: The mandibular condyle is a part of the stomatognathic system whose morphology can change due to adaptation of functional power. Under certain conditions, the condyles may differ on each side, such as in edentulous or partially edentulous patients. In complete dentition, however, there should be less discrepancy in the condyles. Several factors such as bruxism, propping up the chin, sleeping on one side and chewing on one side cause hyperactivity of the masticatory muscles which can cause pain around the temporomandibular joint (TMJ). This can be the cause of morphological differences between the two sides of the condyle, such as the height. The purpose of this study was to describe the height of the condyle in complete dentition patients using questionnaire about chewing habits and TMD symptoms. Methods: This study took samples from panoramic radiograph data of complete dentition patients who came to the radiology installation of RSGM Unpad and were given questionnaires regarding chewing habits and TMD-DI in the period March-May 2023. The height of the condyles on the panoramic radiographs was measured using the measure feature in the ImageJ software, then calculated using the Habets asymmetry index formula. Measurement results and questionnaires are used for grouping samples. Results: There were 46 samples with complete teeth. The results of the calculation of the study data showed that samples with differences in condyle height were found more in male patients and in the 19-29 year age group. Differences in the condyle were also found more in samples that chewed using 1 side and samples with negative TMD-DI results. Conclusion: There are many complete dentition patients who have different appearances of condyle height.KEY WORDS: Condylar height; TMJ; TMD; Panoramic radiograph; Habets asymmetry indKetinggian kondilus, kebiasaan mengunyah dan gejala temporomandibular disorder pada pasien bergigi lengkap: studi observasionalABSTRAK Pendahuluan: Kondilus mandibula merupakan salah satu bagian dari sistem stomatognatik yang morfologinya dapat berubah akibat adaptasi dari daya fungsional. Dalam kondisi tertentu, kondilus dapat memiliki perbedaan di tiap sisinya, seperti pada pasien tidak bergigi maupun bergigi sebagian. Beberapa faktor seperti bruxism, menopang dagu, tidur satu sisi dan mengunyah satu sisi pada pasien bergigi lengkap, menimbulkan hiperaktivitas otot pengunyahan sehingga dapat menyebabkan nyeri di sekitar temporomandibular joint (TMJ). Hal tersebut dapat menjadi penyebab terjadinya perbedaan morfologi antara kedua sisi kondilus, salah satunya adalah ketinggian. Tujuan dari penelitian ini adalah untuk mengetahui gambaran ketinggian kondilus pada pasien bergigi lengkap dengan menggunakan kuesioner mengenai kebiasaan mengunyah dan gejala temporomandibular disorder. Metode: Penelitian ini mengambil sampel dari data radiograf panoramik pasien bergigi lengkap yang datang ke Instalasi Radiologi RSGM Unpad dan sudah diberikan kuesioner mengenai kebiasaan mengunyah dan TMD-DI pada periode bulan Maret-Mei 2023. Ketinggian kondilus pada hasil foto radiograf panoramik diukur menggunakan fitur measure pada software ImageJ, kemudian dihitung dengan menggunakan rumus indeks asimetri Habets. Hasil pengukuran dan kuesioner digunakan untuk pengelompokan sampel. Hasil: Didapatkan sebanyak 46 sampel bergigi lengkap. Hasil perhitungan data penelitian menunjukkan sampel dengan perbedaan ketinggian kondilus lebih banyak ditemukan pada pasien laki-laki dan pada kelompok usia 19-29 tahun. Perbedaan kondilus juga lebih banyak ditemukan pada sampel yang mengunyah menggunakan 1 sisi dan sampel dengan hasil TMD-DI negatif. Simpulan: Terdapat banyak pasien bergigi lengkap yang memiliki perbedaan gambaran ketinggian kondilus. KATA KUNCI: Ketinggian kondilus, TMJ, TMD, radiograf panoramik, indeks asimetri habets ex